The impact of the covid-19 pandemic on airlines and crew - Gonçalves, Julia Pereira; Pirro, Beatriz Gonçalves; Silva, Anna Letícia Januário; Silva, Marina Monteiro da; Delphino, Rodrigo de Benedictis; Oliveira, Rodrigo Ribeiro de (Brazilian Journal of Production Engineering, 2022)
The COVID-19 pandemic impacted the Brazilian airline industry in a way that airlines had to take actions to maintain and rebuild. In this work, we point out the actions taken by the airlines Azul, Gol and Latam. In the analyzed periods, measures such as mass dismissals, PDV (Voluntary Dismissal Request) incentives, salary and working hours reduction and LNR (Unpaid Leave) were observed, in addition to the change of scenario compared to the period of 2019. Some aviation organizations, such as the International Air Transport Association (IATA), have numerically demonstrated how the pandemic has affected the airline industry, which has resulted in the loss of jobs for several professionals. The actions taken by the aforementioned airlines to contain the initial damage, the reaction of union organizations, and finally, the consequences of the advance of vaccination, with the resumption of flights and the rehiring of employees who had been terminated, are reported.